Modelagem espacial de corredores ecológicos em paisagens naturalmente heterogêneas - Lais Ferreira Jales (2013)
Connectivity is a vital component in landscape ecology; it influences the processes of evolution and dynamics of populations. Ecological corridors are strategies for potential contribution to biodiversity conservation that provide connectivity and gene flow between species. However there is no consensus on what methods to use to define their spatial arrangement, particularly in naturally heterogeneous landscapes, where species respond differently in each type of environment. The modeling of ecological corridor by mult-paths in heterogeneous and fragmented landscapes is the main objective of this work. The method used is based on the ecological characteristics of focal species of birds and mammals, at grassland and forest environments, identified by the survey of occurrences in the study area and selected from predefined criteria. Focal areas for connectivity are identified, which were three protected areas, and hotspots for conservation areas to make up the corridor system. Besides these features, the spatial model of ecological environmental variables considered as use and land cover, elevation, slope, presence of protected areas and the possibility of passage of fauna. These variables were manipulated according to the importance values assigned by "expert knowledge" to generate an array of resistance for each species from multicriteria analysis. An assessment of modeling multi-paths shows that there is a closeness between the proposed corridors for grassland and forest environments, showing it to be potentially effective for planning corridors of a particular group of species.